Potential association between endocrine disrupting chemicals (EDCs) and gynecomastia: a systematic review based on partial experimental evidenceendocrine-disrupting chemicals - Wang, Haobo; Wang, Mengdie; Fan, Cuihong; Sun, Yueyao; Feng, Jianping; He, Meng; Li, Ning; Shang, Fangjian; Liu, Bo (Frontiers in Endocrinology, 2026)
Gynecomastia (GYN), the most prevalent benign breast condition in men, is primarily driven by an estrogen-androgen imbalance, which induces glandular proliferation and adipose hypertrophy. This imbalance leads to the proliferation of mammary gland tissue and hypertrophy of adipose tissue. Endocrine-disrupting chemicals (EDCs), as a class of exogenous substances widely distributed in the environment, can disrupt hormonal homeostasis by mimicking estrogen, antagonizing androgens, or interfering with hormone metabolism. Consequently, they represent a significant environmental risk factor for inducing male breast development. Some evidence also suggests that gynecomastia may represent a chronic, non-infectious inflammatory response to estrogenic stimulation, which could further alter the tissue’s hormonal sensitivity. This paper systematically reviews typical EDCs associated with male breast development, including bisphenols, phthalates, and polycyclic aromatic hydrocarbons. It examines their exposure pathways and mechanisms of action, analyzes the clinical characteristics, public health implications, and current prevention and control status of gynecomastia. The review highlights existing issues in current research, such as unclear mechanisms and the complexity of mixed exposure effects. It proposes that future efforts should focus on strengthening research into the molecular mechanisms linking EDCs to male breast development, improving population exposure monitoring systems, and refining prevention and control strategies. This will provide a theoretical basis for the scientific prevention and clinical management of the condition. Furthermore, the paper emphasizes the critical importance of strictly controlling the environmental release of EDCs to protect public health.